FAMILY CEO AND DEBT POLICY OF FAMILY FIRMS IN INDONESIA: THE MODERATING ROLE OF OWNERSHIP - Zahra Latifah Hanum; Abel Tasman (Journal of Economic, Bussines and Accounting (COSTING), 2025)
This study investigated the influence of Family CEOs on long-term debt policy in Indonesian family firms, considering the moderating role of family ownership. Employing a quantitative approach, panel data from 62 family firms listed on the Indonesia Stock Exchange over the 2019–2023 period were analyzed using panel and moderated regression analyses. Results indicated that a Family CEO had a significant positive effect on the proportion of long-term debt, reflecting a long-term strategic orientation aimed at sustaining family control and business continuity. However, family ownership did not significantly moderate this relationship, suggesting that leadership traits influenced debt decisions more than ownership concentration. The findings contribute to the corporate governance and Socioemotional Wealth (SEW) literature by emphasizing the role of family leadership over ownership structure. Limitations of the study include its focus on publicly listed firms, which may limit generalizability to private family businesses. The study offers practical insights for family business stakeholders in designing funding strategies that align with long-term sustainability goals. Keywords: Family CEO, Family Ownership, Debt Policy, Family Business, Corporate Governance